Fluoroquinolone Can Be an Effective Treatment Option for Acute Pyelonephritis When the Minimum Inhibitory Concentration of Levofloxacin for the Causative Escherichia coli Is ≤16 mg/L - Yeonjae Kim; Bongyoung Kim; Seong Heon Wie; Jieun Kim; Moran Ki; Yong Kyun Cho; Seung Kwan Lim; Jin Seo Lee; Ki Tae Kwon; Hyuck Lee; Hee Jin Cheong; Dae Won Park; et al. (MDPI AG, 2021)
The purpose of this study was to determine whether the fluoroquinolone (FQ) minimum inhibitory concentration (MIC) for the causative agent Escherichia coli influences the clinical response of FQ treatment at 72 h in patients with community-acquired acute pyelonephritis (CA-APN). We prospectively collected the clinical data of women with CA-APN from 11 university hospitals from March 2010 to February 2012 as well as E. coli isolates from the urine or blood. In total, 78 patients included in this study received FQ during the initial 72 h, and the causative E. coli was detected. The clinical response at 72 h was significantly higher in patients with a levofloxacin MIC ≤ 16 mg/L than in those with an MIC > 16 mg/L (70.4% vs. 28.6%, p = 0.038). No difference was observed in clinical response at 72 h based on ciprofloxacin MIC. To summarize, FQ can be an effective treatment option for CA-APN when levofloxacin MIC against E. coli is ≤16 mg/L.